Power and power potentiation among strength-power athletes: Preliminary study - Stone, M. H.; Sands, W. A.; Pierce, K. C.; Ramsey, M. W.; Haff, G. G. (International Journal of Sports Physiology and Performance, 2008)
Purpose: To assess the effects of manipulating the loading of successive sets of midthigh clean pulls on the potentiation capabilities of 7 international-level US weightlifters (4 men, 3 women). Methods: Isometric and dynamic peak-force characteristics were measured with a force plate at 500 Hz. Velocity during dynamic pulls was measured using 2 potentiometers that were suspended from the top of the right and left sides of the testing system and attached to both ends of the bar. Five dynamic-performance trials were used (in the following order) as the potentiation protocol: women at 60, 80, 100, 120, and 80 kg and men at 60, 140, 180, 220, and 140 kg. Trials 2 vs 5 were specifically analyzed to assess potentiation capabilities. Isometric midthigh pulls were assessed for peak force and rate of force development. Dynamic lifts were assessed for peak force (PF), peak velocity (PV), peak power (PP), and rate of force development (RFD). Results: Although all values (PF, PV, PP, and RFD) were higher postpotentiation, the only statistically higher value was found for PV (ICCa = .95, P = .011, h2 = .69). Conclusions: Results suggest that manipulating set-loading configuration can result in a potentiation effect when heavily loaded sets are followed by a lighter set. This potentiation effect was primarily characterized by an increase in the PV in elite weightlifters.